Associations of RPEL1 and miR-1307 gene polymorphisms with disease susceptibility, glucocorticoid efficacy, anxiety, depression, and health-related quality of life in Chinese systemic lupus erythematosus patients. (December 2022) - Yan, Zi-Ye; Hu, Wan-Qin; Zong, Qi-Qun; Yu, Guang-Hui; Zhai, Chun-Xia; Wang, Lin-Lin; Wang, Yu-Hua; Zhang, Ting-Yu; Li, Zhen; Teng, Ying; Cai, Jing; Chen, Yang-Fan; et al.
Objective: Our present study intended to examine the associations of RPEL1 and miR-1307 gene polymorphisms (rs4917385 and rs7911488) with susceptibility, glucocorticoids (GCs) efficacy, anxiety, depression, and health-related quality of life (HRQoL) in Chinese systemic lupus erythematosus (SLE) patients. Methods: Initially, 1000 participants (500 SLE cases and 500 controls) were recruited for the case–control study. Then, 429 cases who received GCs were followed through 12 weeks to explore GCs efficacy, depression, anxiety, and HRQoL. We selected the iMLDR technique for genotyping: RPEL1: rs4917385 (G/T) and miR-1307: rs7911488 (A/G). Results: The minor G allele of rs7911488 reduced the risk of SLE ( p = .024). Four haplotypes consisting of rs4917385 and rs7911488 were associated with SLE susceptibility ( p < .025). Both rs4917385 and rs7911488 were associated with anxiety symptoms and physical function (PF) in SLE patients ( p < .025). The rs4917385 was associated with depression and its improvement. No statistical significance was found between RPEL1 and miR-1307 gene polymorphisms with GCs efficacy. Meanwhile, additive interaction analysis showed a significant association between RPEL1 and miR-1307 gene polymorphisms with tea consumption in anxiety. Conclusion: RPEL1 and miR-1307 gene polymorphisms (rs4917385 and rs7911488) might be related to SLE susceptibility in Chinese population. Additionally, the two polymorphisms were possibly associated with depression, anxiety, and HRQoL in Chinese SLE population.